Pelaksanaan Promosi Jabatan dan Dampaknya Terhadap Peningkatan Kinerja Pegawai di Kantor Sekretariat Daerah Kabupaten Lampung Utara - Yadi Lustiadi (e-JKPP, 2015)
Title: Promotion of position And Impact on Employee Performance Improvement At office of Secretariat of Area of Regency Lampung Utara.Problem of this research is : (1) How is the implementation of the promotion positions at Secretariat of Area of Regency of Lampung Utara; (2) How is the impact Job Promotion to employee performance at Secretariat of Area of Regency of Lampung Utara Research Method used in this research is survey the. Population in this research all Public Servant of Civil at Office of secretariat of Area of Regency of Lampung Utara North amounting to 60 people. Research conducted have the character of the census of because all population made by a research responder. Research variable is Occupation Promotion as free variable (X) And Officer Performance is variable trussed (Y)Result of research indicate that there is Influence of signifikan of Occupation Promotion to Officer Performance of Office of secretariat of Area of Regency of Lampung Utara, biggest influence from variable of pembentuk of Occupation Promotion is efficiency dimension work, while smallest dimension from variable of pembentuk of Occupation Promotion is nepotism dimension. Pursuant to research result, can be opened by suggestion that the importance of upheld by order in occupation promotion of according to rule going into effect, so that can be created by a expected job condition.